Role of stem cells in repair of liver injury: Experimental and clinical benefit of transferred stem cells on liver failure - Esrefoglu, Mukaddes (Baishideng Publishing Group Co., Limited, 2013)
Although the liver has a high regenerative capacity, as a result of massive hepatocyte death, liver failure occurs. In addition to liver failure, for acute, chronic and hereditary diseases of the liver, cell transplantation therapies can stimulate regeneration or at least ensure sufficient function until liver transplantation can be performed. The lack of donor organs and the risks of rejection have prompted extensive experimental and clinical research in the field of cellular transplantation. Transplantation of cell lineages involved in liver regeneration, including mature hepatocytes, fetal hepatocytes, fetal liver progenitor cells, fetal stem cells, hepatic progenitor cells, hepatic stem cells, mesenchymal stem cells, hematopoietic stem cells, and peripheral blood and umbilical cord blood stem cells, have been found to be beneficial in the treatment of liver failure. In this article, the results of experimental and clinical cell transplantation trials for liver failure are reviewed, with an emphasis on regeneration.